A macro-element for pile head response to cyclic lateral loading - Norazzlina, M.Sa'don; Pender, M.J.; Abdul Razak, Abdul Karim (2009)
The standard method of modelling the lateral load response of a pile head is to use computer software packages. Many of the conventional software packages model the interaction of the pile shaft and the soil using either the linear or nonlinear Winkler springs approach. An alternative way of analysing the elastic behaviour is to use a simple expression for the pile head stiffness. This approach has been extended in this paper to represent the nonlinear pile head lateral response. Numerical simulations showed that this approach is capable of achieving the same monotonic response prediction as the Winkler spring software. Thus, the response of the whole pile shaft can be represented by a simple set of equations focusing on the pile head. This is referred to as a macro-element. This paper presents an analytical technique of the elastic continuum approach used for the cyclic response of the laterally loaded pile problem. This approach will then be compared with the cyclic Winkler calculations and field data obtained from previously published results.